COMMUNITY SERVICE EDUCATION ON NUTRITIONAL PATTERNS AND TABOOS IN BATAK CULTURE RELATED TO NUTRITION FOR PREGNANT WOMEN IN MEDAN TUNTUNGAN DISTRICT - Noer Desmie; Leni Agustina; Indah Lestari Sitorus (Jurnal Masyarakat Indonesia (Jumas), 2024)
The health of pregnant women is the main indicator of well-being which is highly dependent on nutritional adequacy during pregnancy. However, in Medan Tuntungan District, the nutritional fulfillment of pregnant women is still hampered by cultural factors, especially the belief in the "taboo" of traditional Batak food which often prohibits the consumption of highly nutritious foods. This community service activity aims to increase pregnant women's understanding of balanced nutrition patterns and straighten out the perception of cultural taboos related to nutrition scientifically. Carried out by a team from STIKes Darmo Medan, the intervention was carried out through structured counseling targeting pregnant women and families in Medan Tuntungan District. The results of the activity showed an increase in the enthusiasm and understanding of the participants in sorting out the right nutritional intake without being hampered by unfounded myths. In conclusion, persuasive and cultural educational approaches have proven to be effective as strategies to optimize maternal and fetal health and prevent the risk of pregnancy complications in the region.